Propuesta metodológica para cuantificar áreas afectadas por incendios forestales utilizando imágenes satelitales sentinel-2. Caso de estudio Páramo del Almorzadero Colombia: Methodological proposal to quantify areas affected by forest fires, using sentinel-2 satellite images. Case study at the Almorzadero paramo of Colombia - Ávila Velez, Edier Fernando (UD y la Geomática, 2020)
The present investigation is going to explain how has been calculating the affected area due a forest fired in February of 2019 at the Almorzadero paramo in Santander-Colombia, with the help of radiometric índices AQ, NBRI and NDVI it was to able to characterize the spectral behavior or spectral firm of burned area, with the HH2 radiometer spectrum applied satelital Spectro radiometry with images that proceed of the Sentinel 2 program. Also, it was calculated the variance covariance matrix and the correlation force of the three indices, in order to perform a multi-spectral RGB composition with the proposed indices. As a result, the quantification of the affected area by the fire at the paramo was obtained, approximately 383.4 hectares and the mapping or spatialization of the event. In conclution, it was obtained that when we using radiometric indexes through a composition multi spectral, it facilitates the visual and radiometric interpretation of the vegetation affected by the burning, this due to the spectral variability offered by the different coverages depending of the electromagnetic energy they emit absorbs or transmits.